Whole Irradiated Plant Leaves Showed Faster Photosynthetic Induction Than Individually Irradiated Leaves via Improved Stomatal Opening - Shimadzu, Shunji; Seo, Mitsunori; Terashima, Ichiro; Yamori, Wataru (Frontiers in Plant Science, 2019)
Rapid photosynthetic induction is crucial for plants under fluctuating light conditions in a crop canopy as well as in an understory. Most previous studies have focused on photosynthetic induction responses in a single leaf, whereas the systemic responses of the whole plant have not been considered. In a natural environment, however, both single leaves and whole plants are exposed to sunlight, since the light environment is not uniform even within a given plant. In the present study, we examined whether there is any difference between the photosynthetic induction response of a leaf of a whole irradiated plant and an individually irradiated leaf in Arabidopsis thaliana to consider photosynthetic induction as the response of a whole plant. We used two methods, the visualization of photosynthesis and direct measurements of gas-exchange and Chl fluorescence, to demonstrate that whole irradiated plant promoted its photosynthetic induction via improved stomatal opening compared with individually irradiated leaf. Furthermore, using two Arabidopsis knockout mutants of abscisic acid transporter, abcg25 and abcg40, the present study suggests that abscisic acid could be involved in this systemic response for stomatal opening, allowing plants to optimize the use of light energy at minimal cost in plants in a dynamic light environment.